Analgesia y seguridad de bupivacaína sin epinefrina al 0,125% vs 0,25% en anestesia epidural durante el parto por cesárea - Díaz-Perez, Nelly (2021)
Context: In caesarean section, bupivacaine at 0.125% or 0.25% without epinephrine is used in epidural anesthesia. A higher dose is associated with greater analgesia and a greater frequency of adverse effects. Objective: evaluate the analgesia level and safety of bupivacaine without epinephrine (0.125% or 0.25%) used in cesarean section, in order to recommend the appropriate concentration for this procedure. Subjects and methods: prospective cohort performed on 100 patients undergoing caesarean section at Enrique Sotomayor Gyneco-Obstetric Hospital (October 2015 to January 2016). The population was stratified into two cohorts or groups: A (0.125% bupivacaine) and B (0.25%). Results: two groups of 50 patients were formed. Hypotension was detected in group B (p <0.001) and greater variation in heart rate. In group A, the motor block was maintained at a lower dorsal level (T3) compared to group B (T2) (p <0.001). Regarding the sensory block, the median level of dorsal block was similar in both groups. In group A, 25 patients (50%) were registered who presented adverse effects with respect to group B where there was an adverse effect in 45 cases (90%). Hypotension occurred in 4/50 cases of group A and 16/50 cases of group B (p <0.001). Conclusion: Bupivacaine without 0.125% or 0.25% epinephrine provides similar analgesic results, although the former is significantly related to a lower frequency of adverse effects, especially hypotension (p <0.001), this concentration being recommended for epidural anesthesia during labor due to Caesarean section.